La novella di Ser Cepparello, poi San Ciappelletto - Bolpagni, Marcello (Verbum – Analecta Neolatina, 2013)
The aim of this paper is to analyse the opening short story of Decameron. Here, Boccaccio plays with the reader, hiding himself behind Ser Cepparello, the main character, and giving rise to various interpretations. Does the story concern a criticism against the religious habits and the popular naivety, or is it rather an entertainment, with the only goal of amusing the reader thanks to the power of the word? The paper reviews the most important critical literature, and then it attempts an interpretation of Ciappelletto, who unwillingly became a Saint.